2020
DOI: 10.1021/acsnano.0c03438
|View full text |Cite
|
Sign up to set email alerts
|

Splenic Capture and In Vivo Intracellular Biodegradation of Biological-Grade Graphene Oxide Sheets

Abstract: Carbon nanomaterials, including 2D graphene-based materials, have shown promising applicability to drug delivery, tissue engineering, diagnostics, and various other biomedical areas. However, to exploit the benefits of these materials in some of the areas mentioned, it is necessary to understand their possible toxicological implications and long-term fate in vivo . We previously demonstrated that following intravenous administration, 2D graphene oxide (GO) nanosheets were largely excrete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 105 publications
(307 reference statements)
6
64
0
Order By: Relevance
“…These observations suggest that potential distal effects of "benign" MWCNT were potentially mediated by the immune system, wherein local macrophages trafficked the particles through normal immune pathways. Additionally, while studies evaluating splenic deposition of nanoparticles [26,27], noted particles introduced intravenously or intraperitoneally were found in the red pulp regions, the present studies suggest deposition in the white pulp areas with resulting immune effects of population changes and apoptosis. The end result of this particle translocation was terminal deposition in the spleen resulting in more substantial chronic effects.…”
Section: Discussionmentioning
confidence: 49%
“…These observations suggest that potential distal effects of "benign" MWCNT were potentially mediated by the immune system, wherein local macrophages trafficked the particles through normal immune pathways. Additionally, while studies evaluating splenic deposition of nanoparticles [26,27], noted particles introduced intravenously or intraperitoneally were found in the red pulp regions, the present studies suggest deposition in the white pulp areas with resulting immune effects of population changes and apoptosis. The end result of this particle translocation was terminal deposition in the spleen resulting in more substantial chronic effects.…”
Section: Discussionmentioning
confidence: 49%
“…This means that <1.0 µg of GO was subcutaneously injected per mouse, which was three orders of magnitude lower than the well‐tolerated dose in vivo according to a previous report. [ 31 ] In addition, the route of subcutaneous delivery can avoid the direct entry of GOs into the systemic circulation, greatly reducing potential hazards. A complete blood cell count (Table S2 , Supporting Information) one week after the last DC vaccination revealed no statistically significant differences from values obtained for untreated mice.…”
Section: Resultsmentioning
confidence: 99%
“…PVA has excellent biocompatibility and safety with FDA approval for clinical uses in humans. A very recent study [ 49 ] also demonstrated an encouraging result of in vivo biodegradation of GO which makes the GO based hydrogel promising in biomedical applications.…”
Section: Resultsmentioning
confidence: 99%